Dukungan Sosial Keluarga Dengan Kemandirian Pasien Gangguan Jiwa - Nita Octaviana Permanasari; Zumrotul Chairijah; Puji Purwaningsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
Mental health problems in Indonesia are an important public health problem and should receive serious attention from all governments from central to regional levels. Mental Health Efforts are every activity to create an optimal level of mental health for every individual, family and community using a promotive, preventive, curative and rehabilitative approach which is carried out in a comprehensive, integrated and sustainable manner by the government and/or the community. The aim of this research is to determine the relationship between family social support and independence in mental disorder patients. Method: The type of research used is correlational using a cross sectional design. The population in this study were families containing people with mental disorders. The research instrument is a family social support questionnaire consisting of 14 questions, while the questionnaire about independence consists of 10 questions. Result: significance value or sig. (2-tailed) is 0.000, because the sig value. (2-tailed) 0.000 < 0.05, which means there is a significant (meaningful) relationship between the family social support variable and the independence of mental disorder patients. Suggestion: The family must involve the patient in daily routine activities at home, develop social interactions and involve the patient in managing the environment around the patient so that mental disorders can carry out activities in daily life independently